Fibrin clot structure - pro-fibrinolytic effect of oral contraceptives in apparently healthy women - Sidelmann, Johannes J.; Kluft, Cornelis; Krug, Andrea H.; Winkler, Ulrich; Jespersen, Jørgen; Gram, Jørgen B. (Thrombosis and Haemostasis, 2017)
Fibrin metabolism is influenced by many factors. The velocity of fibrin formation, genetic polymorphisms, fibrinolytic features and the structure of the fibrin clot are determinants of fibrin turnover. Oral contraceptives (OCs) have significant impact on the haemostatic system, by increasing the concentration of coagulation factors, plasminogen and tissue plasminogen activator activity, and decreasing the concentration of haemostatic inhibitors. The present study addresses the influence of OCs on fibrin structure and fibrin metabolism. The study included 70 women treated with seven different OC-formulations. Blood was collected at baseline and after six months of OCs. The plasma concentration of fibrinogen, thrombin-antithrombin complex (TAT), plasminogen, plasmin-antiplasmin complex (PAP), D-Dimer and thrombin generation measures were determined. Fibrin structure measures and fibrin clot lysis not affected by the plasma concentration of plasminogen activators and inhibitors were determined. OCs increased the concentration of fibrinogen, TAT, plasminogen, PAP and D-dimer significantly and affected measures of thrombin generation (p<0.001). The maximal optical density of fibrin (p<0.001), the fibrin fibre density (p=0.03), fibrin fibre diameter (p=0.003), fibrin mass-length ratio (p<0.001) and lysis per hour (p<0.001) increased significantly upon OC-treatment. Lysis per hour was not correlated to the concentration of plasminogen. We conclude that the effect of OCs on the coagulation system is balanced by alterations in fibrin structure, facilitating clot lysis and contributing to the fibrinolytic susceptibility already present in women treated with OC. These alterations may counterbalance the OC-induced increased thrombin generation and reduced coagulation inhibitory potential, contributing to maintenance of the haemostatic balance in women receiving OCs.
Keywords: Oral contraceptives; Coagulation; Fibrinolysis; fibrin structure; clot lysis